Inhibitory Effect of Prostacyclin and Nitroprusside on Type IIB von Willebrand Factor-promoted Platelet Activation - Francesconi, Mariangela; Casonato, Alessandra; Pagan, Stefano; Donella-Deana, Arianna; Pontara, Elena; Girolami, Antonio; Deana, Renzo (Thrombosis and Haemostasis, 1996)
Von Willebrand disease (vWD) of type IIB is a hereditary haemorragic disorder characterised by an excessive interaction of von Willebrand factor (vWF) with the platelet receptor GPIb which promotes platelet activation and aggregation through a phospholipase A2-mediated release of arachidonic acid.The present report shows that prostacyclin and nitroprusside, vaso-dilator-compounds that enhance the cAMP and cGMP concentration respectively, cause a drastic inhibition of the type IIB vWF-induced platelet responses including increase of cytosolic Ca2+ concentration, phosphorylation of pleckstrin (47 kDa) and myosin light chain (20 kDa), secretion of ATP and serotonin, and aggregation parallel to a decrease of arachidonic acid release. Type IIB vWF also elicits tyrosine phosphorylation of proteins with apparent molecular mass of 60,74,82 and 130 kDa. Prostacyclin, which induces per se tyrosine-phosphoryla-tion of proteins of about 38 and 45 kDa, inhibits drastically the type IIB vWF-promoted tyrosine-phosphorylation of the 74 kDa protein while inhibits slightly that of 60 kDa band. The protein tyrosine-kinase inhibitor genistein causes a little decrease in the type IIB vWF-induced release of arachidonic acid.It is concluded that the inhibition exerted by prostacyclin and nitroprusside on type IIB vWF-elicited platelet activation seems to be largely ascribable to prevention of the phospholipase A2 activation with the ensuing decrease of the subsequent protein tyrosine phosphorylation